Dementia Deaths Most Commonly Result from Heart and Lung Disease: Evidence from the South Carolina Alzheimer’s Disease Registry - Daniel A. Amoatika; John R. Absher; Md Tareq Ferdous Khan; Maggi C. Miller (Biomedicines, 2025)
Background: Cardiovascular disease (CVD) significantly impacts Alzheimer’s Disease and Related Dementia (AD/ADRD) mortality. South Carolina has a high incidence of CVD and dementia mortality. The aim of this study, therefore, was to examine the neurological causes of death and the leading causes of death in the South Carolina Alzheimer’s Disease Registry (SCADR). Method: Data from 2005–2018 were extracted from the SCADR using ICD-9 and ICD-10 codes. The top 10 leading causes of death (LCOD) were identified using death certificates. Some neurological causes of death were operationalized by combining related ICD codes, such as CVD_C (I219, I251, I500, I64) and chronic obstructive pulmonary disease (COP_C), (J449, C349), and <semantics>χ2</semantics> was used to compare socio-demographic characteristics and mortality. Adjusted hazard ratios (aHR) and 95% confidence intervals (CI) were estimated using extended Cox Proportional Hazard modeling, adjusting for socio-demographic factors. Results: A total of 207,093 registry cases were included in the analysis. About 70% of cases had Alzheimer’s Disease (AD) diagnosis, and 40% of all cases were 85 years and older. The LCOD was CVD_C (13.4%). The risk of death among cases with vascular dementia (VaD) was 1.17 times the risk of death among those with AD (aHR: 1.172, 95% CI: 1.148–1.196). Among all deaths, cases with COP_C had a significantly higher likelihood of death compared to those with CVD_C (aHR: 1.06, 95% CI: 1.025–1.090). Conclusions: The study highlights CVD_C as the LCOD in frequency, with survival analysis indicating COP_C risk of death as significantly higher compared to CVD_C deaths. There is a need to prioritize CVD and lung-related comorbidity prevention, assessment, and management programs for individuals living with ADRD.